Translating glycated hemoglobin A1c into time spent in glucose target range: A multicenter study - Petersson, Jonathan; Åkesson, Karin; Sundberg, Frida; Särnblad, Stefan (Pediatric diabetes, 2019)
Background Approximately 90% of children and adolescents with type 1 diabetes in Sweden use continuous glucose monitoring (CGM), either as real‐time CGM or intermittently scanned CGM to monitor their glucose levels. Time in target range (TIT) is an easily understandable metric for assessing glycemic control. Objective The aim of this study was to examine the relation between TIT and hemoglobin A1c (HbA1c). Subjects and Methods Subjects were recruited from three diabetes care centers in Sweden. Glucose data were collected for 133 children and adolescents with type 1 diabetes through CGM using Diasend. Subjects with registration time over 80% were included in the analysis. HbA1c was collected from SWEDIABKIDS, the Swedish pediatric diabetes quality registry. TIT was defined as 3.9 to 7.8 mmol/L (70‐140 mg/dL) and time in range (TIR) as 3.9 to 10 mmol/L (70‐180 mg/dL). Results During the period of 60 days, 105 subjects provided complete data for analysis. Mean age was 12.2 (±3.3) years, mean HbA1c was 53.9 (±8.2) mmol/mol or 7.1% (±0.7%). Mean sensor glucose value was 8.6 (±1.3) mmol/L, mean coefficient of variation was 42.2% (±7.2%), mean TIT was 40.9% (±SD 12.2%), and mean TIR was 60.8% (±13.1%). There was a significant nonlinear relation between TIT during 60 days and HbA1c, R2 = 0.69. Conclusion This study suggests a nonlinear relation between time spent in glucose target range and HbA1c. The finding implies that time spent in TIT could be a useful metric in addition to HbA1c to assess glycemic control.